2014
DOI: 10.1242/jcs.154229
|View full text |Cite
|
Sign up to set email alerts
|

The role of nNOS and PGC-1α in skeletal muscle cells

Abstract: Neuronal nitric oxide synthase (nNOS) and peroxisome proliferator activated receptor c co-activator 1a (PGC-1a) are two fundamental factors involved in the regulation of skeletal muscle cell metabolism. nNOS exists as several alternatively spliced variants, each having a specific pattern of subcellular localisation. Nitric oxide (NO) functions as a second messenger in signal transduction pathways that lead to the expression of metabolic genes involved in oxidative metabolism, vasodilatation and skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 96 publications
(113 reference statements)
2
61
0
Order By: Relevance
“…HF feeding to WT mice exhibited augmented serum lipids, altered insulin signaling, and expression of metabolically important enzymes/transcription factors31. iNOS KO mice exhibited altered expression of metabolically important genes (Figs 4 and 7), implying a regulatory role of iNOS/NO in glucose and lipid homeostasis, as reported for eNOS and nNOS KO mice33343536373839.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…HF feeding to WT mice exhibited augmented serum lipids, altered insulin signaling, and expression of metabolically important enzymes/transcription factors31. iNOS KO mice exhibited altered expression of metabolically important genes (Figs 4 and 7), implying a regulatory role of iNOS/NO in glucose and lipid homeostasis, as reported for eNOS and nNOS KO mice33343536373839.…”
Section: Discussionmentioning
confidence: 56%
“…This might be probably due to non-stimulation of PGC-1α expression and its downstream PPAR-α is not regulated within 5 weeks of LFD feeding leading to mitochondrial dysfunction5051. It could be that PGC-1α up-regulation might not necessarily be dependent only on NO signaling pathways3952 or requires more time to affect the downstream pathways leading to change in the mitochondrial function. Mitochondrial OCR levels in KO mice were unaffected after feeding with 5 weeks LFD, thus suggesting mitochondrial dysfunction is not initiated, during the initial stages of IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, immunofluorescence measurements of nNOS detected significant elevations of the protein specifically at the sarco‐lemma. nNOS exists in 4 protein variants, including nNOSα, nNOSβ, nNOSγ, and nNOSμ (52). nNOSα and nNOSμ contain a postsynaptic density‐95/discs large/ zona occludens‐1 homology (PDZ) domain, which allows binding of the enzymes to the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1α seems to be instrumental in the modulation of mitochondrial biogenesis [5], and a further study established that PGC-1α elicited by physical activity seems to be crucial for oxidative metabolism in skeletal muscle fibres [6]. Furthermore, it was demonstrated that mitochondrial biogenesis induced by an enhancement in PGC-1α levels facilitates Wnt-mediated induction of osteoblastic differentiation of mesenchymal C3H10T1/2 cells [7].…”
Section: Genetic Factors and Muscle/bone Phenotypesmentioning
confidence: 93%